Peranan dan Penglibatan Guru Besar dalam Mempertingkatkan Disiplin Pelajar Sekolah Kebangsaan Negeri Kedah - Md. Bakri, Abdullah (2010)
The discipline problem among students has become a hot issue which has been debated by various quarters. This research is carried out to investigate how far role and the responsibility of headmaster in upgrading the discipline among students in primary schools. This research has been carried out in the Kuala Muda district which involves 80 teachers from four selected schools. The data collected has been processed using SPSS software (Statiscal Package For the Social Sciences) version 15.0 to get frequency and the percentage. This study comprises five aspects relating the perception of teachers towards the role and involvement of headmaster in upgrading the discipline among students in primary schools. The results of the study that the role and involvement of headmaster influence substantially the discipline in school.